BioFire® Joint Infection Panel for Samples Other than Synovial Fluid - Nicola Benvenuto; Stefano Di Bella; Luigi Principe; Diego Luppino; Jacopo Conti; Venera Costantino; Manuela Di Santolo; Marina Busetti; Roberto Luzzati; Verena Zerbato (Antibiotics)
Objectives: The early identification of infection-causing microorganisms through multiplex PCR panels enables prompt and targeted antibiotic therapy. This study aimed to assess the performance of the BioFire® Joint Infection Panel (BF-JIP) in analysing non-synovial fluid samples. Methods: We conducted a retrospective cohort study at Trieste University Hospital, Italy, on hospitalised adults with non-synovial fluid samples tested by both BF-JIP and traditional culture methods (November 2022–April 2024). Results: We evaluated 48 samples from 45 patients, including 24 abscess drainage fluids and 10 tissue samples. The BF-JIP showed high concordance (85.4%) and enhanced detection (4.3%) compared to culture methods. The BF-JIP excelled in cerebrospinal fluid (CSF) (100% accuracy and concordance) and in abscess drainage fluid (accuracy: 95.8%; concordance: 91.7%) identification and maintained high performance rates in patients under antibiotics. Conclusions: These findings suggest that BF-JIP is a valuable tool for accurate pathogen detection in various clinical samples, offering the additional advantage of being a rapid method.